Droughts, Floods, and Global Climatic Anomalies in the Indian Ocean World
XVII, 381 p. 20 illus.
Keywords: This book explores histories of droughts and floods in the Indian Ocean World, and their connections to broader global climatic anomalies. It deploys an interdisciplinary approach rooted in the emerging field of climate history to investigate the multifaceted effects of global climatic anomalies on regions affected by the Indian Ocean Monsoon System – regularly conceived of as the macro-region’s ‘deep structure.’ Case studies explore how droughts and floods related to anomalous climatic conditions have historically affected states, societies, and ecologies across the Indian Ocean World, including in relation to food security, epidemic diseases, political (in)stability, economic change, infrastructural development, colonialism, capitalism, and scientific knowledge. Tracing longue durée patterns from the twelfth to the early twentieth centuries, this book makes a significant contribution to our understanding of global climatic events and their effects on the Indian Ocean World. It highlights essential historical case studies for contextualizing the potential effects of global warming on the macro-region in the present and future. Philip Gooding is a Postdoctoral Fellow at the Indian Ocean World Centre, McGill University, Montreal, Canada.